BARRIERS TO IMPLEMENTING TEACHING APPROACHES THAT SUPPORT CHILDREN WITH READING DIFFICULTIES - Khamitova, Aziza (Nаzаrbауеv Unіvеrsіtу Grаduаtе Sсhооl оf Еduсаtіоn, 2023)
Reading difficulties are a common issue that many children experience in their early school years. There are several teaching approaches that help to support these children, but their implementation in classrooms can be challenging due to various barriers. The aim of this study is to understand the barriers that teachers face while implementing effective strategies in teaching students with reading difficulties. As it is a small-scale qualitative research the data were collected from five experienced teachers working in primary mainstream schools in Astana through face-to-face interviews and interviews to the double.
Master оf Sciences іn Educational Leadership